Peran Akuntan Manajemen dalam Menavigasi Kompleksitas Akuntansi Global : Perspektif VUCA dan Digitalisasi - Divana Aisha Dewayani; Gita Fatwa Yanti (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This research is motivated by the increasing complexity of the global and digital business environment, characterized by high uncertainty (VUCA). The role of management accountants has evolved, demanding new competencies to address the challenges of globalization, digital transformation, and sustainability issues. The purpose of this research is to examine the evolution of the management accountant's role in a VUCA environment, identify key required competencies, and formulate adaptive strategies. This research uses a literature review method to analyze various relevant academic sources. The findings indicate that management accountants require strong digital competencies, cross-cultural understanding, risk management skills, and a deep understanding of sustainability issues. Recommended adaptive strategies include the development of training programs, increased inter-functional collaboration, and the adoption of data analytics technologies. The implications of this research for management accounting practitioners are the need for competency development and strategy adaptation to meet the challenges of a dynamic business environment.